Pengaturan Agama Leluhur Pascaputusan Mahkamah Konstitusi No. 97/PUU-XIV/2016 Ditinjau dari Perlindungan Hak Asasi Manusia - Herdika, Muhamad Ridwan; Husodo, Jadmiko Anom (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2021)
ABSTRACTThis research describes and examines the problem, first about how to recognize local religion in post-Constitutional Court verdict No.97/PUUXIV/2016. Second, analysis of verdict of the Constitutional Court No.97/PUU - XIV/2016 on the fulfillment of human rights of followers of local religion. This research is a normative analytic and descriptive-analytical normative legal research. Secondary data types contain primary, secondary and tertiary legalmaterials. The data collection technique used is the study of literature, then the technical analysis used is the deductive method. The results of the research obtained by the author, the first verdict of the Constitutional Court No.97/PUU-XIV/2016 has been approved to significantly recognize the local religion in the legislation. Secondly, the implications of the Constitutional Court’s verdict No.97/PUU-XIV/2016 effect on the fulfillment of the rights of believers (ancestral local religion) throughout Indonesia.Keywords : MK verdict No. 97/PUU-XIV/2016; local religion; human rights.